PENERAPAN METODE ANALISIS EMPIRIS ANTRIAN DAN KUALITAS PELAYANAN TERHADAP KEPUASAN NASABAH PADA BANK - Vera Budyarti; Lutfi Alhazami (Melati Institute, 2022)
Customer satisfaction is a person's feelings of pleasure or disappointment that arise after comparing the expected product performance (results) to the expected performance. This research is quantitative with associative design. This type of quantitative research is research obtained from the processing of numbers. In this study the variables are queues (X1) and service satisfaction (X2) which are independent variables and customer satisfaction (Y). The results showed that the queuing variable and service quality together affected the customer satisfaction variable due to the significance value <0.05. The limitations of the study are several factors that further researchers can pay more attention to to further refine their research because the research itself certainly has shortcomings that need to be improved.